TRACING MAQASID AL-SHARI‘AH IN THE FATWAS OF INDONESIAN COUNCIL OF ULAMA (MUI) (JOURNAL OF INDONESIAN ISLAM, 2017)
Majelis Ulama Indonesia (MUI) or the Indonesian Council of Ulama has been issuing fatwas since its formation by the state in 1975. In the process of fatwa issuing within MUI, there are fundamental principles to be taken into account to make sure the protection Islamic teaching in all of its aspects, namely theology, law and social issues. The account to sacred texts is the outmost. In addition, the employment of maqasid al-shari‘ah is introduced to ensure the applicabi-lity and utility of faftwa, especially in the area of human interaction and social religious life. The employment of maqasid al-shari‘ah by MUI is apparent in its many fatwas, such as on medical and marriage issues. However, MUI only uses the archaic version of maqasid al-shari‘ah which is exclusive to the interest of Muslims. Progressive interpretation of maqasid al-shari‘ah which is designed for dealing with modern issues is not employed. Consequently, some MUI fatwas are deemed controversial in the context of plural and modern Indonesia.